THE USE OF ETIQUETTE WORDS IN ENGLISH AND KARAKALPAK LANGUAGES: THE USE OF ETIQUETTE WORDS IN ENGLISH AND KARAKALPAK LANGUAGES - Utepova, Utepova D. (Журнал иностранных языков и лингвистики, 2025)
Etiquette words are commonly used both in written and spoken languages. The way how people use the words of etiquette depends on one's awareness, knowledge and culture. Etiquette words are used when addressing someone, in situations like apologising, greeting, thanking, requests and many other. In English and karakalpak languages they are different in meaning and context, and in some speech acts they carry the same meaning. N.I. Formanovskaya stated "Speech etiquette is understood as the regulating rules of speech behavior, a system of nationally specific stereotyped, stable communication formulas, adopted and prescribed by society to establish contact with interlocutors, maintain and interrupt contact in the chosen tone